Organizational justice and affective commitment: the mediating role of perceived organizational support among UAE government employees - Hazem Aldabbas; Abdallah M. Elamin; Ahmed Zain Elabdin Ahmed (Cogent Business & Management)
The aim of this study is to examine the relationship between organizational justice and affective commitment through the mediating role of perceived organizational support (POS). The specific mechanism through which organizational justice influences affective commitment remains unclear, specifically in relation to the public sector. Grounded in social exchange theory, this research examines how POS acts as a mediator between organizational justice and affective commitment. This study analyzed data from 302 government employees (166 males [55.0%] and 136 females [45.0%]) working in the public sector in the United Arab Emirates. The study employed hierarchical regression and Baron and Kenny’s mediation approach to test the hypothetical model. The findings indicate that organizational justice influences POS, which in turn affects affective commitment. Additionally, POS serves as a key mediator between organizational justice and affective commitment, uncovering an important mechanism through which fairness perceptions strengthen POS and commitment. These insights deepen our understanding of justice in organizational settings and emphasize the value of boosting POS to foster a more engaged and committed workforce.